Equvalent Issues in Translating Proverbs and the Strategies used - Astiari, Komang; Suardana, I Putu Eka (Universitas Pendidikan Ganesha, 2024)
This study investigated some equivalent issues in translating English proverbs into Indonesian and strategies applied to deal with it. As proverbs are statement that consist of moral value and traditional views to describe situation in daily life, several properties between source language and target language are shared. This study explores the constraints translators face when translating English proverbs into Indonesian due to the lack of equivalents. This research uses qualitative methods. Qualitative research is a type of research based on the collection, analysis, and interpretation of data in narrative form. Data collection is done by looking for English proverbs contained in the book